Cross-cultural construct complexity: an initial empirical analysis of Perú - de Luque , Mary sully (1999)
Cross-cultural scholars continually request empirical research thatbroadens the complexity of culture. We examine the effects of culture following the broad conception of cultural constructs as cultural syndromes that are multifaceted. Based on past theoretical and empirical research, this study identifies three cultural syndromes, IndividualismCollectivism, Tolerance for Ambiguity and Status Identity, with the objective of utilizing original and existing conceptually sound measures of these constructs. The dimensionality of these constructs was assessed through the development and analysis of responses from a sample 0f226 Peruvian managers and experienced employees. Results provide support for the multi-dimensionality of these dimensions.